Schnittstellen von Erfahrung und Erwartung. Ein Plädoyer für Storys im interkulturellen Literaturunterricht - Wojtczak, Maria (Studia Germanica Posnaniensia, 2017)
The specific situation of a German academic working outside of Germany emerges via the differential and non-simultaneous absorption (or incorporation) of methodological schools and traditions. This article shows a possible means of executing the balancing act between the learned "third culture" and your own tradition. It is about the interfaces between experience and expectation which one can find them through understanding the narrative structures. One can glean profound understanding via: narrative structure, deep structure of the text, on the basis of stories and cultural tropes, and through to structured narrative itself and to the story than the way the literature appropriation in the foreign language specific perspective. We only know as much as we are able to express. The language cultural identity exists because of the language and it is equal as narrative identity.